Realization of Assertive Speech Acts By The Main Character in The Turning Red Film - Fadillah, Syifa Fellashufa; Syafri, Frimadhona; Pratama, Hendi (English Education Journal, 2024)
In the field of pragmatics, speech act analysis is fundamental to knowing the intended meaning behind a speaker's utterance. The objectives of this particular study encompass elucidating the manifestation of assertive speech, direct and indirect assertive speech acts, and the utilization of Asian Politeness by Meilin Lee in the acclaimed film Turning Red. Methodologically, this study adopted a qualitative approach with pragmatics study. The findings illuminated that there were 71 instances of utterances indicative of speech acts. Furthermore, the primary character exhibited a predilection towards employing assertive speech acts to articulate her beliefs and viewpoints, thereby expressing and elucidating various concepts in her utterances. Mei predominantly employed direct speech in her interactions with friends. However, in certain scenarios, she resorted to indirect speech when declining her friends' invitations. Moreover, she employed indirect speech to mask her emotions. In an effort to safeguard her mother’s feelings and conceal actions that perturbed her, Mei frequently resorted to fabrications